(untitled) (Journal of Medical & Health Sciences Review, 2025)
The fast growth of livestock production worldwide demands new approaches to boost the growth performance and feed ratio as well as sustainability and animal welfare. Traditional breeding methods have been applied to genetic advancement although they have been slow and relied on natural genetic variations that restrict their application in addressing the present-day farming needs. This paper examines how gene editing using CRISPR/Cas9 can be used to enhance sheep growth and feed efficiency by targeting a negative muscle development regulator, the myostatin (MSTN) gene. The microinjection and electroporation of sheep zygotes were done with subsequent embryo culture, transfer and phenotypic analysis of the resulting progeny. There was high editing efficiency, whereby the mass of muscles, average daily gain, and a 20-30 percent increase on feed conversion ratio of edited lambs was significantly higher than those of controls. Off target analysis showed that there were low numbers of unwanted mutations that validate the specificity and safety of CRISPR/Cas9 system. These results indicate that a fine-tuned genome editing of MSTN can be an effective method to increase growth characteristics and feed efficiency in sheep, which provides a promising instrument to achieve a fast-based genetic enhancement and provide livestock production with sustainability. This study forms the basis of the multi-gene editing approaches in the future to maximize economically valuable characteristics in livestock.